a-a平方分之a平方-2a+1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 23:38:04
a-a平方分之a平方-2a+1a-a平方分之a平方-2a+1a-a平方分之a平方-2a+1=(a-1)²/[-a(a-1)]=(a-1)/(-a)=(1-a)/a
a-a平方分之a平方-2a+1
a-a平方分之a平方-2a+1
a-a平方分之a平方-2a+1
=(a-1)²/[-a(a-1)]
=(a-1)/(-a)
=(1-a)/a
a-a平方分之a平方-2a+1
化简(a-a分之2a-1)除以a的平方+a分之1-a平方
a平方b+ab平方分之a平方-b平方除以(2ab分之a平方-b平方-1)
已知a+a分之2=1,求a平方分之5a平方-6a-3a平方
(-2分之1ab平方-3a平方b)平方
a-1分之2+1-a平方分之a+3
a的平方+2分之a的平方-1
a+1分之1+a的平方-2a-3分之a的平方-a除以a-3分之a
1-a+2b分之a-b除以a平方+4ab+4b平方分之a平方-b平方
(a-1分之2a-a+1分之a)×a分之a平方-1 化简
a的平方*b+a*b的平方分之a的平方-b的平方/(2*a*b分之a的平方+b的平方-1)
(a的平方-a)除a-1分之a的平方-2a+1化简
a+3分之1-9-a平方分之6,1-(a-1-a分之1)÷a平方-2a+1分之a平方-a+1计算.a-1分之a÷a平方-1分之a平方-1-a-1分之1计算,化简(a平方-ab分之b+b平方-ab分之a)×a+b分之ab
a+3分之1-9-a平方分之6,1-(a-1-a分之1)÷a平方-2a+1分之a平方-a+1计算.a-1分之a÷a平方-1分之a平方-1-a-1分之1计算,化简(a平方-ab分之b+b平方-ab分之a)×a+b分之ab
A平方+B平方分之2B+A-B分之1-A+B分之1
(a-b)分之1-(a+b)分之1+(a平方-b平方)分之2b=
a+1分之a-a的平方-1分之a-2除以a的平方-2a+1分之a的平方-2a
a-1分之1-2a+a平方-a平方-a分之根号a平方-2a+1-a 其中a等于2-根号3